(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The Russian-Ukrainian conflict is the most significant security crisis since World War II. Intense fighting has irreparable effects on water, air, soil, and the ecosystem. They are leading to a massive loss of life and unfolding social and humanitarian disaster in the Black Sea region. Even more significant, however, is the information disaster in cyberspace, which has gone far beyond these borders and even affected the whole world. This study reviews available normative documents to examine the maximum amount of documents related to managing Russia’s and Ukraine’s combat operations in information warfare. Access to the state electronic databases of Russia and Ukraine, which provide access to many normative documents, was used to fulfill the set objective. These are the “Official web portal of the Parliament of Ukraine” (Verkhovna Rada of Ukraine) and “The Federal Assembly” of the Russian Federation (The State Duma). The aggregate number of sources examined is 83564. Based on the criteria for inclusion, the total number of articles analyzed was reduced to 216, as they specifically pertain to security in information and cyberspace. The research findings on information risk between the two countries indicate that their primary focus was ensuring cyber security following the outbreak of war. However, one of the initial priorities was to address the safeguarding of e-government and the information security of citizens. Subsequently, steps were implemented to combat false information and coordinate their media, which was crucial to the operation's success. The analysis indicates that Russia is presently experiencing defeat in the information war between the Western world and Ukraine. However, it is achieving resounding success within its borders and is garnering support from Chinese citizens as well as other isolated nations like Iran and North Korea. Partial achievements have been observed in Asia and Africa. However, the situation could rapidly shift due to the superior influence of Western powers on popular social platforms, including Facebook, Twitter, Instagram, YouTube, and Google. This conflict has transcended into more than a mere battle between two nations and their military forces. It embodies the form of an impending conflict— the war behind the war.